Functional Modification Effect of Epoxy Oligomers on the Structure and Properties of Epoxy Hydroxyurethane Polymers - Victor Stroganov; Oleg Stoyanov; Ilya Stroganov; Eduard Kraus (Advances in Materials Science and Engineering)
We introduce different ways to solve the actual fragility problem of the epoxy-amine polymers by curing epoxidian oligomers with aliphatic amines without additional heat input. The pathways are the oligomer-oligomeric modification of epoxy resins-epoxy oligomers (EO), with their conversion to oligoethercyclocarbonates (OECC) by carbonization with carbon dioxide. The cocuring of these oligomers as a result of aminolysis competing reactions is “epoxide-amine” (forming a network polymer) and “cyclocarbonate-amine” (forming the linear hydroxyurethane, extending the internodal chains). Formation of internal and intermolecular hydrogen bonds was established on hydroxycarbonates (HA) and linear polyhydroxyurethanes (PHU) model compounds by IR and NMR spectroscopy. The results of the hydrogen bond system formation processes explain the change in the relaxation and physicomechanical properties of hard polymers modified by the epoxy-amine compositions (OECC), containing aromatic and aliphatic links. This paper presents a possible OECC modificator, the optimal EO:OECC ratio and its influence on the cross-link frequency, the polarity, the fragment and chain flexibilities and, as a consequence, the possible stiffness regulation for selected epoxy polymers. Thus, the causes of the increase in deformation-strength and adhesion characteristics were established by a factor of 1.5 to 3.0 due to an increase in cohesive strength (as a result of the combined network operation with covalent and physical bonds), as well as reduction of residual stresses (by adding the aliphatic fragments as additional relaxants), and reducing the defectiveness of the boundary layers (polymer-substrate).